2007
DOI: 10.1562/0031-8655(2002)0760320pohbth2.0.co2
|View full text |Cite
|
Sign up to set email alerts
|

Photobleaching of Hypericin Bound to Human Serum Albumin, Cultured Adenocarcinoma Cells and Nude Mice Skin¶

Abstract: Hypericin is a promising photosensitizer for photodynamic therapy (PDT) characterized by a high yield of singlet oxygen. Photobleaching of hypericin has been studied by means of absorption and fluorescence spectroscopy in different biological systems: in human serum albumin solution, in cultured human adenocarcinoma WiDr cells and in the skin of nude mice. Prolonged exposure to light (up to 95 min, 100 mW/cm2) of wavelength around 596 nm induced fluence‐dependent photobleaching of hypericin in all studied syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 57 publications
2
14
0
1
Order By: Relevance
“…Moreover, even at an administered light fluence of 20 J/cm 2 (dose far beyond LD 90 as can be seen from Fig. 7) no photobleaching of the drug was observed, suggesting that hypericin is a very stable photosensitizer in agreement with other work ( 27 ). It should be noted, however, that photoinduced disaggregation may mask the extent of photodegradation.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, even at an administered light fluence of 20 J/cm 2 (dose far beyond LD 90 as can be seen from Fig. 7) no photobleaching of the drug was observed, suggesting that hypericin is a very stable photosensitizer in agreement with other work ( 27 ). It should be noted, however, that photoinduced disaggregation may mask the extent of photodegradation.…”
Section: Discussionsupporting
confidence: 88%
“…The combination of limited PpIX levels and rapid photobleaching yields a low PDT dose which may fail to achieve sufficient cell killing during a light exposure that photobleaches all accumulated PpIX. In contrast to PpIX, hypericin is very photostable 21 and laboratory studies have indicated that, when activated by artificial light, it has enhanced antitumour activity 22–24 . Moreover, tests investigating the topical application of hypericin have shown promising results 13 .…”
Section: Discussionmentioning
confidence: 99%
“…The interaction of Hyp with HSA has already been profoundly studied (11)(12)(13)(14)(15)(16)(17)(18). It was found that Hyp specifically interacts and forms a 1:1 complex with HSA (binding constant K b = 7.5 · 10 5 M M )1 ) (12).…”
Section: Introductionmentioning
confidence: 99%